Urgensi Tawadhu’ Bagi Kawula Muda - Sutrisno, Sutrisno (Jurnal SOLMA, 2024)
Background: Young people are one of the nation's assets that must be maintained and developed, their potential is human resources that are physically and spiritually healthy and we really need to pay attention to them, therefore the Urgency of Tawadhu' equips them to respect each other, have extraordinary sympathy and empathy, create something interesting, become a role The model is to strengthen Islamic characteristics and values ​​which are kaffah. Method: Community Service through the task of a Scientific Oration as a resource person (First Doctoral Alumni of the Tarbiyah Faculty) at the XXX IAIDU Asahan Bachelor Graduation activities, which was held on Thursday 24 August 2023 using the pilot method from Sahabat's Story, namely an approach that focuses on efforts to understand Tawadhu ' with patterns 1. The Importance of Having Tawadhu' Characteristics, 2. Contribution of Graduates/Wati with Tawadhu', 3. Design of Tawadhu's Paradigm. Results: God willing, we can realize the hopes of Muslims, as the saying goes, syubbān alyaum rijāl al-gadd that today's young people are tomorrow's leaders, so that they are accustomed to "saying greetings first when meeting other people, don't like insulting other people, like helping other people." , Does not show favoritism in friends, does not like to show off, so is always calm, simple and serious in avoiding acts of takabbur (arrogance) or sum'ah. Conclusion: Allah makes good morals a perfect barometer of a servant's faith, with Tawadhu', we actually carry out one of the morals of the Prophets.